OC-032 A cross-sectional observational clinical audit to determine missed opportunities in routine screening for alcohol use disorders in the emergency admissions department. (17th June 2017) - Owens, L; Patterson, K; Ninkovic-Hall, G; Richardson, P
Abstract : Introduction: In our hospital identification of possible Alcohol Use Disorders (AUD) in the emergency admissions department (EAD) is inconsistent as it requires; a) clinicians assessing patients to have a suspicion of AUD and b) for them to refer the patient to the Alcohol Specialist Nurse team (ASNT) for screening. Therefore, we are unable to estimate the true scale of AUD in presenting patients, but believe that is likely to be significantly underestimated. This has implications not only for the patients, but for our ability to provide accurate burden of disease estimates to our service commissioners. We therefore conducted and audit to determine if AUDs were going undetected, unreported and therefore potentially untreated. Method: For 60 randomly allocated sessions between April 2016 and February 2017 consecutive patients attending the EAD had an alcohol screen by a dedicated nurse. To identify only those patients where AUD had been missed, the usual pathway for referral to the ASNT was not altered. Any patient who had been previously identified was not approached by the screeners. Patients underwent a staged screening process; the Paddington Alcohol Test (PAT)[1] was used as a pre-screen, if positive AUDIT-C was administered followed by the full 10 question AUDIT questionnaire where AUDIT-C >5[2]. For patients scoring AUDIT>15 referral to the ASN enabled assessment utilising Severity of Alcohol Dependence Questionnaire (SADQ)[3] to determine level of dependence. Results: A total of 1004 patients met PAT criteria for screening, 72% (n=217) were male, ave. age was 46.4 years (range 17 to 83). 29% (n=299) scored=>8 AUDIT, of which 11% (n=117) scored AUDIT>15 meeting criteria for assessment of dependence. Of these 106 underwent SADQ assessment. 31% (n=33) scored <15 indicating mild dependence 64% (n=68) scored=>15 and<30 indicating moderate dependence 5% (n=5) scored >30 indicating severe dependence. An average 5 patients per session with an AUD were missed thought usual clinical practice. Therefore, 1 in 8 patients not identified were at risk of alcohol withdrawal, and 1 in 3 were amenable to interventions as recommended by NICE. Conclusion: Routine screening is failing to detect patients with AUDs in the EAD, and therefore missing opportunities for treatment. The ASNT currently receive referrals for ~10 patients per day, however our audit has shown that this is a significant shortfall as we detected an average 5 further patients per session. Most importantly, we are missing patients in high risk drinking categories. Universal screening for AUDs in EADs is doable and necessary to reduce clinical risk and optimise opportunities to reduce alcohol-related harms. Disclosure of Interest: None Declared